Evaluasi Sistem Kerja berdasarkan Macroergonomic Analysis and Design dengan Integrasi Macroergonomic Analysis of Structure di Gudang PT. Mulia Multi Medika - Mohamad, Silvana; Mohamad, Firmansyah; Firdaus, Aqfi Nur; Fais, Moh. Ainul (Universitas Teuku Umar, 2025)
This study aims to evaluate the work system in the PT. Mulia Multi Medika warehouse using an integrative approach of Macroergonomic Analysis and Design (MEAD) and Macroergonomic Analysis of Structure (MAS). The method stages include: (1) identification of the environment and organizational structure; (2) definition of the work system through SWOT analysis; (3) setting performance expectations and mapping subsystems; (4) ergonomic risk assessment using the Workplace Ergonomic Risk Assessment (WERA) and Job Strain Index (JSI); and (5) analysis of the work environment in the form of temperature and noise. In addition, interviews with managers and workers were conducted to capture subjective perceptions of workload and system effectiveness. The results show that worker 1 has a WERA score of 41 (moderate risk) and a JSI of 18 (high), while worker 2 has a WERA score of 35 (moderate) and a JSI of 6.75 (low). The temperature of 18–22°C and noise of 68–72 dB are still within safe limits. The MEAD–MAS analysis revealed role imbalances and technological limitations. Recommendations for improvement include the use of material handling aids, role redistribution, and continuous evaluation to reduce ergonomic risks while increasing productivity.